Current issues in the realization of the rights of children with autism spectrum disorder in the Republic of Kazakhstan - Bitabarova, Ж.А.; Tussupova, А.Ж.; Mynbayeva, Н.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Against the backdrop of the steady increase in the number of children with autism spectrum disorder (ASD), improving the legal regulation of their status and ensuring the effective implementation of their state-guaranteed rights has become an issue of particular importance. The purpose of this study is to identify the systemic challenges in the implementation of the rights of children with ASD in the Republic of Kazakhstan, to analyze the current legislation and law enforcement practice, and to develop scientifically grounded recommendations for their improvement. The main areas of the research include the analysis of legal mechanisms for early diagnosis, medical, social, and educational support for children with ASD, the assessment of the effectiveness of state regulation in this field, and the identification of priority directions for the development of national legislation. The scientific significance of the study lies in its comprehensive legal analysis of the legal status of children with ASD, which fills an existing gap in Kazakhstan's legal scholarship, while its practical significance is reflected in the development of specific recommendations aimed at improving legislation and law enforcement practice. The methodological framework is based on general scientific and special legal methods, including analysis and synthesis, the systemic approach, formal legal and comparative legal methods, content analysis, legal modeling, and the analysis of law enforcement practice. The study identifies the key challenges affecting the implementation of the rights of children with ASD, including deficiencies in diagnostic procedures, the absence of a unified interagency approach, a shortage of qualified professionals, limited access to evidence-based intervention methods, and the need to transition to the International Classification of Diseases, 11th Revision (ICD-11). The authors propose a set of organizational and legislative measures aimed at enhancing the effectiveness of state policy in this area. The value of the research lies in establishing a scientific foundation for the further development of the legislation of the Republic of Kazakhstan on the protection of the rights of children with ASD and in developing practical mechanisms to improve access to medical, social, and educational services, strengthen law enforcement practice, and promote the full social inclusion of children with autism spectrum disorder.